The professionals speak: practitioners’ perspectives on professional election campaigning - Tenscher, Jens; Koc-Michalska, Karolina; Lilleker, Darren G.; Mykkänen, Juri; Walter, Annemarie S.; Findor, Andrej; Jalali, Carlos; Róka, Jolán (Sage, 2016)
Faced with some fundamental changes in the socio-cultural, political and media environment, political parties in post-industrialized democracies have started to initiate substantial transformations of both their organizational structures and communicative practices. Those innovations, described as professionalization, become most obvious during election campaigns. In recent times, the number of empirical studies measuring the degree of political parties’ campaign professionalism has grown. They have relied on a broad spectrum of indicators derived from theory which have not been tested for their validity. For the first time, we put these indicators to a ‘reality check’ by asking top-ranked party secretaries and campaign managers in 12 European countries to offer their perceptions of professional election campaigning. Furthermore, we investigate whether any differences in understanding professionalism among party campaign practitioners can be explained by macro (country) and meso (party) factors. By and large, our results confirm the validity of most indicators applied in empirical studies on campaign professionalism so far. There are some party- and country-related differences in assessing campaign professionalism too, but the influence of most factors on practitioners’ evaluations is weak. Therefore, we conclude that largely there is a far-reaching European Union-wide common understanding of professional election campaigning.